A PENGARUH KOMPETENSI KEPRIBADIAN GURU TERHADAP KEDISIPLINAN PESERTA DIDIK DI SEKOLAH DASAR GEREJA MASEHI INJILI DI TIMOR OESAPA - Tae, Metriana; Heryon Bernard Mbuik; Alvin Javier Hano (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Tae, Metriana (2026) Title: The Influence of Teacher Personality Competence on Student Discipline at GMIT Oesapa Elementary School. Thesis. Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, Citra Bangsa University, Kupang. Supervisor I: Heryon Bernard Mbuik, S.PAK., M.Pd., Supervisor II: Alvin Javier Hano, S.Pd., M.Pd.. Teacher personality competence is the ability related to the attitudes, values, and personality possessed by teachers in carrying out their duties as educators, thereby improving student discipline. However, suboptimal teacher personality competence results in low student discipline. Based on the results of pre-observations conducted during the approximately three-month PPL activities, from August 2 to October 28, 2025, at GMIT Oesapa Elementary School, it was found that the level of student discipline still needs to be improved. From the data observed in the fifth grade of GMIT Oesapa Elementary School, there were still some who were late to school, did not complete or were late in submitting assignments, violated school rules such as not wearing complete attributes or talking when the teacher was explaining, and paid less attention during the learning process. These data indicate that the disciplinary behavior of students at the school is still not optimal. This condition can certainly affect the smoothness of the learning process and the achievement of educational goals at school. This study used a quantitative approach with the ex post facto method. The research population was all fifth grade students of GMIT Oesapa Elementary School, totaling 29 people and used as research samples. The data collection technique used a Likert scale questionnaire and data analysis used simple linear regression with the help of SPSS version 25. The results of the study showed that there was a positive and significant influence between teacher personality competence on student discipline with a significance value of 0.039 (<0.05). The regression coefficient value of 0.990 indicates that every increase in teacher personality competence will be followed by an increase in student discipline, while the coefficient of determination (R²) value of 0.878 indicates a contribution of 87,8%. It can be concluded that teacher personality competency significantly influences student discipline, thus improving teacher personality competency is necessary to create effective learning.